Upper Paleolithic materials from Cova Negra (Xàtiva) and its implications in the sequential stratigraphic processes - Valentín VILLAVERDE BONILLA; Aleix EIXEA VILANOVA (Zephyrus, 2017)
We approach Upper Paleolithic lithic materials from Cova Negra belonging to 30’s, 50’s, 80’s and 2013-2016 field seasons. This article focuses on the characterization of blanks, cores, and tools with a preliminary chronology, specially, from retouched materials. The main interest is the Upper Paleolithic occupation and the evaluation of postdepositional processes documented in the cavity and how they impacted to Middle Paleolithic classic levels and to all Upper Paleolithic levels facilitating an evaluation of the extent of the processes of postdepositional alteration registered in the cavity and how these processes affected a good part of the levels of the classic middle Palaeolithic and to all the levels of the Upper Paleolithic. Data allow us a better depositional comprehension and they explain the problematic interpretations in relation with upper levels from Middle Paleolithic.